Agricultural development during early industrialization in a low-wage economy: Saxony, c. 1790-1830 - Michael Kopsidis; Ulrich Pfister (European Historical Economics Society (EHES), 2013)
The characteristics of regional paths of industrialization had a deep impact on agricultural development during early industrialization in Germany. From 1840 rising incomes in the course of a "high wage-low energy cost" industrialization based on coal and steel and a rapid urbanization triggered a demand driven agricultural revolution in Northwest Germany. In contrast, Saxony's early industrialization c. 1800-1860 followed a "low wage-high energy cost" trajectory based on textile production and slow urbanization. The low level and slow growth of income meant that up to 1830 the adaptation of agricultural innovations neither followed demand impulses transmitted through markets, nor did they facilitate inter-regional specialization according to comparative advantage. Rather, regional agriculture ac-commodated to population growth by expanding the cultivation of subsistence crops, mainly potatoes, probably at the detriment of animal husbandry. Whereas the increase of sown area indicates an intensification of land use yield ratios remained at best stable between the early 1790s and the late 1820s. Hence, local supply could barely cope with population growth, and since grain market integration did not evolve over time imports did not com-pensate for the shortcomings of domestic production. Our evidence of a deteriorating food standard goes a long way toward explaining the decline of the biological standard of living during Saxony's early industrialization.
Keywords: N93; O13; Q11; 330; Agriculture and industrialization; regional specialization; Agricultural Revolution